Estudo das 3 Leis de Isaac Newton: uma sequência de ensino investigativa usando a robótica educacional - Real, Antonio Flávio Vila (2023)
This text refers to the master's thesis, representing an investigative study within the scope of the professional master's degree in Science and Mathematics Teaching of the Postgraduate Program in Science and Mathematics Teaching (PPGECM) at the University of Passo Fundo (UPF). The core of the research addresses the difficulties faced by teachers in promoting students' interest and evaluation in physics classes, as well as the lack of opportunities for students to have research experiences. In this way, technological tools, such as educational robotics, can become good allies in the teaching process, which is the purpose of this work. The main motivation for this research was due to the lack of interest on the part of 1st year high school students in learning physical concepts. In this sense, the following question was formulated that guides this investigation: how can an Investigative Teaching Didactic Sequence, covering Educational Robotics, help 1st year high school students in understanding Isaac Newton's 3 Laws? To answer this question, an educational product was created, being a didactic sequence to address the concepts of Newton's 3 Laws, for the 1st year of High School, consisting of nine meetings. The proposal was prepared in light of the principles of the Research-based Teaching Sequence, which has as key activities: Contextualized Problem, Systematization of Knowledge, Contextualization, Assessment. This research predominantly used a qualitative approach, with the logbook, questionnaires answered by students and evaluation of the work carried out as instruments for data collection. The methodology used involved the creation of a structured sequence, starting with the presentation of a contextualized problem that motivates students to explore the laws of motion. Next, the Systematization Activity stage promoted practical experimentation and consolidation of knowledge. Educational robotics served as a central resource, allowing students to translate theoretical concepts into physical actions. Contextualization extended the application of laws to real-world contexts, while Assessment offered a comprehensive measure of learning, incorporating formative feedback to improve the process. The educational product that accompanies this dissertation refers to a didactic sequence aimed at high school Physics teachers and brings together activities focused on the study of Newton's 3 Laws. At the end of this research, satisfactory results were obtained after analyzing the activities and practices carried out, work presented, and evidence that points to the potential of the proposal. This product is available on the PPGECM/UPF page and in the EduCapes repository http://educapes.capes.gov.br/handle/capes/743590.